Looking Back to the Future: The South African Big Band Jazz Aesthetic Curating the South African Jazz Songbook for Jazz Orchestra - Wyatt, Marcus (College of Music, 2024)
This creative research project involved the curating of repertoire for a special performance in the Royal Albert Hall, of a South African Jazz Songbook, featuring the Metropole Orkest and selected soloists, and the resulting music preparation process for the concert. The objective of this project was to provide an overview of the story and sound of South African jazz to a mainly international audience. The primary challenge was to encapsulate the sound of a country that is comprised of numerous cultures and languages, all of which interact with jazz in a distinct and individualistic manner. This creative endeavour, in essence, was an attempt to address the question of what defines South African big band and orchestral jazz. Further focal questions were explored, specifically the questions of how South African jazz is distinguished from other approaches to jazz, and what characteristics South African jazz shares with global and American big band and orchestral styles of jazz. The creative research process was conducted in several stages. The first stage involved curating the repertoire, with considerable attention paid to creating a programme that encompassed as wide a representation of South African jazz styles as possible, whist maintaining broad audience appeal. It was important for the project that the list of works selected would best capture the essence of South African jazz. Further consideration was given to which songs and artists have helped to establish the South African jazz sound both locally and on the global stage. The next stage concerned the selection of appropriate soloists for the performance. Following this stage, was the music and score preparation. The process of arranging a South African jazz songbook for jazz orchestra involved careful consideration in terms of what comprises a distinct South African jazz sound in relation to the traditionally Western classical ensemble. It was crucial to determine the most effective approach to the writing and arranging of these works. This involved the identification of devices and tropes that define an African orchestral jazz sound. Further consideration was given to whether there would be a noticeable departure from this sound if the music were to be arranged or composed by someone unfamiliar with the intricacies of South African jazz, such as an arranger from a European or American background. The final stages of the project included the rehearsal process, and preparation for the final performance.